Usability assessment on GOE-EGDMS system / Zamani Mustaffa - Mustaffa, Zamani (2012)
This study was discussed on the Usability Assessment on GOE-EGDMS System which the aim is for investigating usability problems on GOE-EGDMS system. The problems in the system were caused user reluctant to use the system. But our scope was to investigate the design problem from users' perspective in using the system. The studies also help MOA's developer to improve the system according to the problem found in the usability testing. The test participants in the usability testing consist of five government servants and they were observed by researchers while using the GOE-EGDMS system in Usability Lab. The results from this usability testing had been analyzed using top - down analysis. From the analysis we found that, the existing design was so confusing and difficult for users to understand it. Based on finding in the research, we suggest that, improvement is needed on system design, so that it can be easily understood and used by the users.